2016
DOI: 10.1186/s12934-015-0402-6
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a novel biosynthetic pathway for gentamicin B production in Micromonospora echinospora

Abstract: BackgroundIsepamicin is a weakly toxic but highly active aminoglycoside antibiotic derivative of gentamicin B. Gentamicin B is a naturally occurring minor component isolated from Micromonospora echinospora. 2ʹ-NH2-containing gentamicin C complex is a dominant compound produced by wild-type M. echinospora; by contrast, 2ʹ-OH-containing gentamicin B is produced as a minor component. However, the biosynthetic pathway of gentamicin B remains unclear. Considering that gentamicin B shares a unique C2ʹ hydroxyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
155
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(156 citation statements)
references
References 23 publications
1
155
0
Order By: Relevance
“…We have previously demonstrated that Cas9 poses toxicity in cyanobacteria15. We sought to circumvent the toxicity issue by employing an alternative RNA guided DNA nuclease, Fncpf1 from Francisella novicida 16.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated that Cas9 poses toxicity in cyanobacteria15. We sought to circumvent the toxicity issue by employing an alternative RNA guided DNA nuclease, Fncpf1 from Francisella novicida 16.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated CRISPR genome editing in Synechococcus 2973 by adapting pCRISPOmyces, a cas9 based system from Streptomyces, to function in Synechococcus 1315. However, this system was suboptimal because of toxicity issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of this enzyme requires a minimum of three structural genes and three genes for FeMo-cofactor biosynthesis [23]. However, optimum activity requires the presence of additional genes, as the specific activity of a nitrogenase expressed in Escherichia coli was only about 10% of that observed in the Paenibacillus species from which it was derived; and improvements were made with additional transgenes [24]. Alternatives to Nif have active site cofactors that lack Mo, instead containing both vanadium and iron (Vnf), or iron only (Anf) [23].…”
Section: Plant Growth Promotionmentioning
confidence: 99%